Cardiac Arrest and Death in Neurosurgery: An Analysis of Perioperative Anesthetic Adverse Events in Thailand - Akavipat, Phuping; Sookplung, Pimwan; Boonsombat, Thanatporn; Raksakietisak, Manee; Tongrong, Cataleya; Lerdsirisopon, Surunchana; Lekprasert, Varinee; Punjasawasdwong, Yodying; Ittichaikulton, Vichai (Journal of Neuroanaesthesiology and Critical Care, 2018)
Background Complexities of pathological causes in cardiac arrest and death in neurosurgery require individualized management. To decrease the incidents, this study was performed to describe characteristics and factors reducing adverse outcomes together with potential corrective strategies of perioperative cardiac arrest and death in neurosurgical patients.Methods An observational study was performed in 22 hospitals. Peer-reviewed consensus was formed using database from Perioperative Anesthetic Adverse Events in Thailand (PAAd Thai) study. The data contain demography, anesthetic, surgical details, opinions on contributing factors, and factors that minimized incident as well as suggested corrective strategies.Results From 2,000 incidents, 64 (3%) cardiac arrest events were reported with a 50% chance of return of spontaneous circulation. The most common cardiac rhythm documented was asystole. Essentially, electrocardiography was the most frequent early detector. Surgical-related factors (81.3%), mostly intraoperative bleeding, played a major role in potential causes of arrest. In addition, anesthesia, patient conditions, and system-related factors were found in 65.6%, 57.8%, and 8.3% of the incidents, respectively. Moreover, the severity of the patients (73.3%) was considered to be the most common anesthesia-related risk factor. The prevention of an incident included rule enforcement for patient safety, mandatory knowledge, and also anesthesia personnel's skills development.Conclusion The optimum fluid assessment and resuscitation, cerebral protection protocols, clinical awareness, and quality assurance together with human resource management are all essential to eliminate the catastrophic cardiac arrest and death in neurosurgery.
Keywords: complication; risk; cardiopulmonary resuscitation; neuroanesthesia; national audit